Engaging student-teachers in English oral presentation: A teachers feedback - Kusrin Kusrin; Muhammad Reza Pahlevi; Siti Nursanti (Research And Innovation In Language Learning (RILL), 2021)
This present study reports on how teacher gives feedback on oral presentation in an EFL classroom. Observation sheet deployed feedback on oral presentation given by teacher in classroom. Data analysis discovered that the teacher concerned on giving comments in pronunciation, paraphrasing, and power point design. In addition, the analysis showed that students had good encouragement in doing oral presentation.